Elucidating the genomic regions through genome-wide association study (GWAS) for root traits in cowpea (Vigna unguiculata (L) Walp) mini-core collection - Zaffar, A.; Paliwal, R.; Abberton, M.; Akhtar, S.; Mengnoo, A.R.; Sheikh, A.N.; Sofi, P.A.; Bhat, M.A.; Mir, R.R. (Elsevier, 2024)
Enhancing the root traits through selection and breeding efforts can significantly improve the acquisition of soil resources, consequently boosting crop production in marginal environments. Cowpea is one of the important legume crops in arid and semi-arid regions, grown mostly in marginal environments under drought conditions. The roots play a crucial role in plant's ability to survive and adapt under such water stressed conditions. The understanding of cowpea genetic architecture related to root system architecture (RSA) remains limited due to difficulties in accurately measuring root traits. In the present study, a set 110 diverse mini-core collection of cowpea from IITA, Nigeria was evaluated for thirteen (13) different root-shoot traits under controlled conditions in the green house. Significant variation was recorded for all the root traits in the mini-core set. Most promising genotype for most of the root traits, viz., root volume, dry root weight, root biomass density and tap root diameter were identified. The correlation analysis revealed significant positive association (p < 0.001) of root weight with shoot weight (0.85), root volume (r = 0.61), and tap root diameter (0.56). In the principal component analysis (PCA), first three principal components explained the variance of 64.31%, with PC1 contributing 44.43%, PC2 10% and PC3 9.88%. All the root-shoot traits contribute positive variation to PC1especially dry root weight and dry shoot weight that had high component loading and in PC2 root shoot ratio had high loading. The root-shoot trait data was used with 6,574 good quality SNP data for discovery of genes/QTLs/marker-trait associations for root traits. The analysis of results of genome wide association study (GWAS) led to the identification of 52 unique SNPs associated significantly (p < 10−4) with thirteen root-shoot traits. Highest number of SNPs was found associated with root weight and chromosome 5 was identified as SNP hotspot for harboring majority of significant SNPs. We further delve candidate genes within 50 kb around the identified SNP that led to the identification of several important candidate genes underlying genomic regions responsible for root-shoot traits in cowpea. The promising cowpea genotypes for root traits and promising MTAs/candidate genes will prove useful in cowpea improvement programs including improvement of drought tolerance in cowpea.